Fiber Optical Sensors for Monitoring the State of Objects and The Environment - Abduraimov Jamoliddin Boymurotovich; Aliboyev Botir Atham ogli; Xasanov Mirkomil Mirxidoyat ogli; Yusupov Yarashbek Toxirbayevich (Zien Journals, 2021)
The article describes new approaches to measuring environmental parameters and technicaldevices in monitoring systems, based on the use of the capabilities of fiber-optic systems with variousmethods of processing an optical signal. It is shown that the use of such systems will significantly simplifythe measurement process, as well as obtain new possibilities for measuring and analyzing physicalquantities. Recent developments in optical fiber array sensors are reviewed, including quasi-distributed strainmeasurement using Bragg gratings, chirped grating systems, intra-array sensing concepts, long period arraysensors, and interferometric sensor systems based on grating reflectors.
Keywords: Fiber optic sensor; light guide; laser radiation; sensor; spectral analysis